The impact of global climate change on Upper Euphrates Basin temperature data - Aydin, Alp Buğra; Erguven, Rojhat (Inderscience Publishers, 2024)
The climate has been changing throughout history; this change is accelerating with the addition of natural causes as well as human-caused causes. Scientists have used some trend analysis methods to predict possible future consequences of climate change. In this study, Mann-Kendall, Spearman’s rho and IPTA methods were used and the effect of climate change on the temperature values of the provinces in the Upper Euphrates Basin in Turkey was investigated. According to the results, there are multiple trends in all stations, and the IPTA method is more sensitive compared to the other two methods. © 2024 Inderscience Enterprises Ltd.
Keywords: climate change; IPTA; temperature; trend analysis; Upper Euphrates